There Was a Party for Langston, King O' Letters - Reynolds, Jason; Pumphrey, Jerome; Pumphrey, Jarrett (New York : Atheneum Books for Young Readers, 2023)
A celebration of Langston Hughes and African American authors he inspired, told through the lens of the party held at the New York Public Library's Schomburg Center for Research in Black Culture in 1991.
Keywords: Hughes, Langston, -- 1902-1967 -- Juvenile fiction; Hughes, Langston, -- 1902-1967 -- Fiction; Poets -- Juvenile fiction; African Americans -- Juvenile fiction; Parties -- Juvenile fiction; Libraries -- Juvenile fiction; Poets -- Fiction; African Americans -- Fiction; Parties -- Fiction; Libraries -- Fiction; JUVENILE FICTION / Imagination & Play; JUVENILE FICTION / Holidays & Celebrations / Other, Non-Religious; Harlem (New York, N.Y.) -- Juvenile fiction; Harlem (New York, N.Y.) -- Fiction; Picture books; Biographical fiction